The Impact of Marketing Strategies and Service Quality on Customer Satisfaction: A Case Study of Massage Chair Service Users - Angraini, Suci; Reniati, Reniati; Khairiyansyah, Khairiyansyah; Saputra, Darman (Master of Management Department, Faculty of Economics and Business, Universitas Bangka Belitung, 2023)
This research investigates the influence of marketing strategy and service quality on customer satisfaction among massage chair service users at PT Nusantara Sehat-Perfect Relax at Depati Amir Airport, Pangkalpinang City. The study employed a nonprobability sampling method using the incidental sampling approach, and the data analysis involved validity and reliability tests, classic assumption tests, multiple linear regression analysis, t-test, F-test, and R-squared test with SPSS version 24. The results of the descriptive analysis revealed moderate mean values for marketing strategy (3.37), service quality (3.35), and consumer satisfaction (3.34). The research found that marketing strategy (X1) and service quality (X2) positively and significantly affected customer satisfaction. Moreover, the F-test demonstrated that marketing strategy and service quality jointly and significantly influenced customer satisfaction (p < 0.05, p = 0.000). These findings highlight the importance of effective marketing strategies and high service quality to enhance customer satisfaction. The research contributes valuable insights for service industry practitioners and managers to improve customer experiences and loyalty.